2017
DOI: 10.1186/s12947-017-0111-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preload on 3-dimensional deformation parameters: principal strain, twist and torsion

Abstract: Background: Strain analysis is feasible using three-dimensional (3D) echocardiography. This approach provides various parameters based on speckle tracking analysis from one full-volume image of the left ventricle; however, evidence for its volume independence is still lacking. Methods: Fifty-eight subjects who were examined by transthoracic echocardiography immediately before and after hemodialysis (HD) were enrolled. Real-time full-volume 3D echocardiographic images were acquired and analyzed using dedicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
6
2
Order By: Relevance
“…In 2017, Hyo et al reported results of their study conducted with 3DSTE and concluded that HD deteriorated GLS, GCS, GRS, and AREA strain. 15 Our results were not fully in concordance with theirs as they also reported worsening in twist and torsion. The somewhat small strain data we observed can be attributed to the different software we used.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In 2017, Hyo et al reported results of their study conducted with 3DSTE and concluded that HD deteriorated GLS, GCS, GRS, and AREA strain. 15 Our results were not fully in concordance with theirs as they also reported worsening in twist and torsion. The somewhat small strain data we observed can be attributed to the different software we used.…”
Section: Discussioncontrasting
confidence: 87%
“…This negative effect was not related to ultrafiltration volume, Kt/V, and demographic and biochemical data. In 2017, Hyo et al reported results of their study conducted with 3DSTE and concluded that HD deteriorated GLS, GCS, GRS, and AREA strain 15 . Our results were not fully in concordance with theirs as they also reported worsening in twist and torsion.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, those infants also demonstrated a decrease in radial strain and SR following ligation, providing further evidence of differential load dependency of deformation parameters based on the plane assessed. In human adults undergoing hemodialysis (HD, resulting in a decrease in LV preload), “circumferential and radial strain values were significantly decreased after HD.” The group did not assess strain rate values. In adult patients undergoing aortic valve replacement for severe aortic stenosis (resulting in a reduction in LV afterload and an increase in LV preload), radial/circumferential strain and systolic strain rate significantly improve immediately following the procedure with a further improvement 6 months postprocedure.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, techniques to quantify local mechanics, such as strain profiles, degree of rotation and angular velocity within the ventricular wall, have proven to be sensitive indices in detecting ventricular performance [ 16 ]. These metrics can be measured by tracking myocardial motion non-invasively through speckle tracking echocardiography [ 17 , 18 ], tagged-MRI [ 19 ], 4D ultrasound with 3D strain mapping [ 20 ] as well as tracking transmural myocardial fiber organization through diffusion tensor MRI [ [21] , [22] , [23] ] and 3D ultrasound backscatter tensor imaging [ 24 ]. These techniques are especially important when considering cardiovascular diseases such as heart failure with preserved ejection fraction (HFpEF), recently declared by the National Heart, Lung and Blood Institute as the “greatest unmet need in cardiovascular medicine” [ 25 ].…”
Section: Cardiac Mechanostructurementioning
confidence: 99%